Augmented Reality to Assist Skin Paddle Harvesting in Osteomyocutaneous Fibular Flap Reconstructive Surgery: A Pilot Evaluation on a 3D-Printed Leg Phantom - Cercenelli, Laura; Babini, Federico; Badiali, Giovanni; Battaglia, Salvatore; Tarsitano, Achille; Marchetti, Claudio; Marcelli, Emanuela (Frontiers in Oncology, 2022)
Background: Augmented Reality (AR) represents an evolution of navigation-assisted surgery, providing surgeons with a virtual aid contextually merged with the real surgical field. We recently reported a case series of AR-assisted fibular flap harvesting for mandibular reconstruction. However, the registration accuracy between the real and the virtual content needs to be systematically evaluated before widely promoting this tool in clinical practice. In this paper, after description of the AR tool development for both tablet and HoloLens 2 smart glasses, we evaluated the achievable registration accuracy with the two display solutions and the success rate in executing the AR-guided skin paddle incision task on a 3D printed leg phantom. Methods: From a real computed tomography dataset, 3D virtual models of a human leg, including fibula, arteries and skin with planned paddle profile for harvesting, were obtained. All virtual models were imported into Unity software to develop a marker-less AR application suitable to be used both via tablet and via HoloLens 2 headset. The registration accuracy for both solutions was verified on a 3D printed leg phantom obtained from the virtual models, by repeatedly applying the tracking function and computing pose deviations between the AR-projected virtual skin paddle profile and the real one transferred to the phantom via a CAD/CAM cutting guide. The success rate in completing the AR-guided task of skin paddle harvesting was evaluated using CAD/CAM templates positioned on the phantom model surface. Results: On average, the marker-less AR tool showed comparable registration errors (ranging within 1-5 mm) for tablet-based and HoloLens-based solution. Registration accuracy seems to be quite sensitive to ambient light conditions. We found a good success rate in completing the AR-guided task within an error margin of 4 mm (97% and 100% for tablet and HoloLens, respectively). All subjects reported greater usability and ergonomics for HoloLens 2 solution. Conclusions: Results revealed that the proposed marker-less AR tool may guarantee an acceptable registration error for assisting skin paddle harvesting in the clinical setting. Optimal lightening conditions and further improvement of marker-less tracking technologies have the potential to increase the efficiency and precision of this AR-assisted reconstructive surgery.